(untitled) (Nigerian Journal of Pharmaceutical Research, 2023)
Background: Different parts of Elaeis guineensis (EG) plants are used ethno-medicinally for treating numerous illnesses including abdominal contraction. Objectives: Thus, this study evaluated the inhibitory potential of the fruit-extract of EG on the uterine contractility in ex-vivo mouse models. Material and Methods: The effect of EG extract on spontaneous uterine contractions, oxytocin (OT)-induced uterine contractions, high potassium chloride induced uterine contractions and oxytocin-induced calcium free contraction were evaluated in adult non-pregnant female albino mice. Results: EG in a concentration dependent mode diminished spontaneous uterine contractions, while amplitude and frequency of contractions were inhibited significantly, but the frequency of contraction was at the highest concentration of EG. EG also produced a significant inhibition of the frequency of OT-induced contraction in calcium-free media. Conclusion: The aqueous fruit extracts of EG inhibited uterine contraction in the uterus through inhibition of intracellular calcium stores.